Calcium supplementation dose and vegetable intake determine preeclampsia - laila fitriani; Ari Probandari; Budiyanti Wiboworini (Intelektual Pustaka Media Utama, 2019)
Preeclampsia is one of the cause of high maternal mortality rates. Risk factors for preeclampsia include a lack of nutrients such as vitamin A, calcium, sodium and potassium. Calcium intake in pregnant women is not only obtained from calcium supplementation, but also obtained from consumed foods such as vegetables. to analyzed the relationship between calcium supplementation dose and vegetable intake with preeclampsia in third trimester of pregnant women. observational analytic used a prospective cohort design. A total of 65 third trimester pregnant women participated in the study in Bantul, Yogyakarta. The calcium supplementation dose was obtained through interview using a questionnaire, while vegetable intake was obtained through the food frequency and food recall 2x24 hours. 16 third trimester pregnant women experienced preeclampsia. The mean calcium dose consumed per day was 476.2 mg. The average intake of vegetables per day for pregnant women was 250.9 gr. Kaplan-Mier with the log rank method states that there was a significant difference between calcium supplementation dose (p=0.007) and preeclampsia. There was a significant difference between vegetable intake (p=0.007) and preeclampsia. there was a significant relationship between calcium supplementation dose and vegetable intake with preeclampsia in third trimester pregnant women.